2004
DOI: 10.1074/jbc.m308898200
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori VacA Activates the p38/Activating Transcription Factor 2-mediated Signal Pathway in AZ-521 Cells

Abstract: Persistent Helicobacter pylori colonization in the stomach induces gastritis and peptic ulcer and interferes with ulcer healing. Most strains of H. pylori produce a cytotoxin, VacA, that induces cytoplasmic vacuolation in epithelial cells with structural and functional changes, leading to gastric injury. VacA is known to cause cell death by mitochondrial damage. We hypothesized that VacA might disrupt other signaling pathways; to that end, we examined the effects of VacA on MAPKs to elucidate their role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 54 publications
3
80
1
3
Order By: Relevance
“…In contrast, Nakayama et al reported that p38 did not participate in VacA-induced cytochrome c release and Bax activation in gastric epithelial cells [38]. However, several studies have demonstrated that p38 MAPK activates Bax to induce mitochondrial cytochrome c release and apoptosis in neuroblastoma cells [39], keratinocytes [40], and lens epithelial cells [41].…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Nakayama et al reported that p38 did not participate in VacA-induced cytochrome c release and Bax activation in gastric epithelial cells [38]. However, several studies have demonstrated that p38 MAPK activates Bax to induce mitochondrial cytochrome c release and apoptosis in neuroblastoma cells [39], keratinocytes [40], and lens epithelial cells [41].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, we established that RPTP␤ functions as a receptor for VacA (24,29,31,32) and that RPTP␤, expressed in gastric tissue, is responsible for gastric injury caused by VacA (9). Notably, as there was no difference in vacuole development between wild-type mice and RPTP␤-deficient mice, we concluded that RPTP␤ is not essential either for the internalization of VacA or for vacuolation in gastric epithelial cells.…”
Section: Discussionmentioning
confidence: 86%
“…Purification of VacA-VacA was purified from H. pylori ATCC49503 strain culture supernatant using an anti-VacA antibody column as described (24,29). VacA was precipitated from culture supernatant with 50% saturated ammonium sulfate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations